2020
DOI: 10.5415/apallergy.2020.10.e43
|View full text |Cite
|
Sign up to set email alerts
|

Low immunoglobulin G4 subclass level is associated with recurrent wheezing in young children

Abstract: Background The most important infectious trigger of asthma is the virus and patients with immunoglobulin deficiencies are prone to recurrent respiratory infections. Objective We investigated the relationship between immunoglobulin G subclass and recurrent respiratory symptom exacerbation and explored possible therapeutic effects of intravenous immunoglobulin administration. Methods Twenty-eight infants less than 24 months old with 2 or more r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…11 Recently, Kim et al showed that there was an association between recurrent wheezing and IgG4 deficiency and demonstrated a significant inverse correlation between wheezing episodes and IgG4 levels in the infantile wheezer group. 14 As in previous reports, our study also found that infants with low IgG4 levels, requiring frequent hospitalizations, may have had severe asthma-like symptoms. We considered that delayed maturation of the immune system in infancy could lead to viral-induced recurrent wheezing and asthma-like symptoms.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…11 Recently, Kim et al showed that there was an association between recurrent wheezing and IgG4 deficiency and demonstrated a significant inverse correlation between wheezing episodes and IgG4 levels in the infantile wheezer group. 14 As in previous reports, our study also found that infants with low IgG4 levels, requiring frequent hospitalizations, may have had severe asthma-like symptoms. We considered that delayed maturation of the immune system in infancy could lead to viral-induced recurrent wheezing and asthma-like symptoms.…”
Section: Discussionmentioning
confidence: 93%
“…There was a report of which results of intravenous immunoglobulin (IVIG) administration to severe wheezy infants with low level of IgG4 14 . Within 1 week after administration of IVIG, IgG4 increased.…”
Section: Discussionmentioning
confidence: 99%
“…The most common IgG1 deficiency results from a generalized deficiency of antibodies, IgG2 deficiency is associated with recurrent viral and bacterial infections, both IgG2 and IgG3 deficiency predisposes to recurrent respiratory tract infections, and IgG4 deficiency has been found in chronic bronchial and lung diseases [ 187 ]. Two studies showed that low levels of the IgG4 subclass were associated with recurrent wheezing, requiring hospitalization in infants and young children [ 188 , 189 ].…”
Section: Resultsmentioning
confidence: 99%
“…75,78 One report found HBoV1 at high frequency in infants with wheezing and low IgA and IgG4 levels, suggesting a possible involvement in recurrent wheezing during childhood. 79 However, the cytokine response in respiratory secretions and peripheral blood has been poorly approached, which encourages further research. In this regard, recent findings indicate that HBoV1 patients hospitalised with ALRI exhibit an increased percentage of cells positive for CD19 and CD23 markers (CD19 þ CD23þ) and a lower proportion of CD3-CD16 þ CD56þ cells, suggesting B-lymphocyte differentiation/activation and decreased NK cell function.…”
Section: Natural History Of Infection Pathophysiology and Clinical Fe...mentioning
confidence: 99%
“…On the other hand, transient low levels of IgG subclass 4 are associated with recurrent wheezing requiring multiple hospitalisations in childhood and IgA deficiency may predispose to recurrent respiratory infections and wheezing 75,78 . One report found HBoV1 at high frequency in infants with wheezing and low IgA and IgG4 levels, suggesting a possible involvement in recurrent wheezing during childhood 79 . However, the cytokine response in respiratory secretions and peripheral blood has been poorly approached, which encourages further research.…”
Section: Natural History Of Infection Pathophysiology and Clinical Fe...mentioning
confidence: 99%